Designing accessible musical instruments by addressing musician-instrument relationships - McMillan, Andrew; Morreale, Fabio (Frontiers in Computer Science, 2023)
This article explores the concept of intimacy in the relationship between a musician and their instrument, specifically in the context of designing digital and accessible musical interfaces (DMI/AMI) for disabled musicians. We argue that current DMI/AMI design frameworks are lacking in their consideration of this relationship and that this deficiency can prevent designers from understanding the specific needs and desires of disabled musicians. The paper presents an autoethnographic study of the lived experiences of the first author, a disabled musician, to provide insight into the evolution of his music-instrument relationships and his definition of ``success'' in this context. The authors propose that incorporating these types of lived experiences into the AMI design process, and considering cultural probes or provocations related to phenomenological experiences and characteristics that contribute to a successful musician-instrument relationship, could lead to more effective and tailored DMI/AMI designs for disabled musicians.